2010
DOI: 10.1055/s-0037-1619065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and geographic distribution of haemophilia in Costa Rica

Abstract: Haemophilia is the most frequent hereditary haemorrhagic illness and it is due to the deficiency of coagulation factors VIII (haemophilia A, HA) or IX (haemophilia B, HB). The prevalence of this disease varies according to the country, those having better survival rates having also higher prevalences. Specifically in Costa Rica, there are around 130 HA and 30 HB families. This study reports the prevalence and a spatial distribution analysis of both types of the disease in this country. The prevalence of haemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…19 Others studies in Arab countries and some Latin-Americans regions show even lower mean age. 20,21 In our study, PWH-B presented older mean age than those with HA, results that coincide with others reports. 8 The nding in HB could agree with the statement that HB is a less severe disease phenotypically than HA.…”
Section: Discussionsupporting
confidence: 93%
“…19 Others studies in Arab countries and some Latin-Americans regions show even lower mean age. 20,21 In our study, PWH-B presented older mean age than those with HA, results that coincide with others reports. 8 The nding in HB could agree with the statement that HB is a less severe disease phenotypically than HA.…”
Section: Discussionsupporting
confidence: 93%
“…Our study group included more than one-third of subjects younger than 12 years old, as expected considering the demographics of haemophilic patients in Costa Rica. 24 The young age of our patient group may explain the relative low median value of HJHS despite the lack of adequate replacement therapy. On average, joint health status, as revealed by HJHS, was moderately compromised, reflecting the later onset of prophylaxis if compared with age-matched patient populations who receive regular standard prophylaxis since early childhood the young age of the study group.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 87%
“…In this study conducted in San José, Costa Rica, we observed that in patients with haemophilia who have limited access to replacement therapy including regular prophylaxis, muscle function deterioration is present despite the progression of structural joint damage and occurs very early in life. As of 2010, 130 patients with haemophilia A and 30 with haemophilia B were known in the country and we were able to examine around 40% of them at least once. Our study group included more than one‐third of subjects younger than 12 years old, as expected considering the demographics of haemophilic patients in Costa Rica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation